Предмет: Алгебра,
автор: DiScOrD9fLy
Упростите выражение, пожалуйста. (Распишите подробно)
(a^-3b^4 / 5) * (5 / a^-2b^3)
^ - степень
Ответы
Автор ответа:
0
(a^-3b^4 / 5) * (5 / a^-2b^3)=
(5*(a^-3b^4))/(5*(a^-2b^3))=
(a^-3b^4)/(a^-2b^3)=
a^(-3b^4+2b^3)=
a^(-b^3(3b-2))
(5*(a^-3b^4))/(5*(a^-2b^3))=
(a^-3b^4)/(a^-2b^3)=
a^(-3b^4+2b^3)=
a^(-b^3(3b-2))
Похожие вопросы
Предмет: Английский язык,
автор: sagindikovauljan
Предмет: Биология,
автор: Sergeikavalevskij
Предмет: Математика,
автор: kamila9925
Предмет: Математика,
автор: tolkacheva2005
Предмет: Математика,
автор: totalplus00